Conditioning competitive behaviour in experimental Bertrand markets through contextual frames - Jiménez-Jiménez, Francisca; Rodero-Cosano, Francisco Javier (Elsevier, 2023)
Explaining framing effects is one of the main challenges faced by decision theories. This research experimentally examines how different contextual frames influence competitive behaviour in a Bertrand duopoly game (repeatedly played under a stranger matching), unexplored so far. The design comprises four frames: one abstract (a beauty-contest framing), two meaningful (the standard Bertrand framing and an access-to-river framing) and one evocative (a take-from-fund framing). Our findings show that, at first, the evocative frame differentiates from the rest mostly in market prices. While the evocative frame induces subjects to behave closer to the theoretical predictions initially, the others need some repetitions until convergence is achieved. Differences across frames eventually vanish at the end. During the transition, in the Bertrand frame, a quicker decay in prices is observed due to the behavioural reactions to historical market prices. Lastly, irrespectively of frames, behavioural reactions to immediate past information allow to explain strategic interaction in the long-run: a force-balance situation which is consistent with the related literature on price floors in Bertrand games.
Keywords: Economía de mercado; Framing effects; Bertrand competition; Laboratory experiments; Contextual frame